Evaluation of Filling Methods Applied to Some Marbles from Diyarbakir Region of Turkey - DAG, AHMET; CEVHEROGLU, SUMEYRA; AYHAN, MUSTAFA (Asian Journal of Chemistry, 2010)
In this study, performance of the filling methods polyester, epoxy and ultraviolet resins applied to two different types of limestone were analyzed. The limestone (sedimentary) used originates from two different types of marble that are widely produced and processed in the Diyarbakir region. The effects of the filling methods on loss of material that occurred during the processing stage and the total process costs were also determined.